Proton exchange membrane and preparation method and application thereof

By using sulfide polyethylene ketone ketone pyrology and ionic liquid hybrid fillers in the proton exchange membrane, the problem of "weighing" the problem of "weighing" the problem between the proton conductivity and methanol penetration of the directly methanol fuel cell, and achieved high performance The development of proton exchange membranes has excellent mechanical properties and long -term stability.

CN119340435APending Publication Date: 2025-01-21CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411476647.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

In direct methanol fuel cells, existing proton exchange membranes are difficult to effectively control methanol cross-penetration when improving proton conductivity, and there are problems of durability, mechanical strength and cost-effectiveness during long-term use.

Method used

A proton exchange membrane based on sulfonal polyethyl ether loaded polyxolic acid and ionic liquid hybrid filler, which is modified by using water insoluble ionic liquid to modify soluble polychic acid to reduce the solubility of poly acids, thereby forming a proton conduction that is conducive to proton conduction Chemical micro -environment.

Benefits of technology

It is possible to significantly reduce the methanol permeability without sacrificing proton conductivity, improve the mechanical properties and long-term oxidation stability of the membrane, and meet the high performance requirements of direct methanol fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340435A_ABST
    Figure CN119340435A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of proton exchange membranes for fuel cells, in particular to a proton exchange membrane as well as a preparation method and application thereof. The filler is synthesized through ionic liquid modified polyacid, and the method is a strategy for modifying soluble polyacid by selecting water-insoluble ionic liquid to reduce the solubility of the polyacid. The method does not sacrifice proton conductivity, and a favorable chemical microenvironment is formed for proton conduction. The inorganic filler is homogeneously dispersed and stable in the polymer matrix due to the enhanced ionic interaction. The filler can promote a continuous hydrogen bond network in sulfonated polyaryletherketone sulfone, and a favorable chemical microenvironment is formed for proton conduction. Compared with a traditional hybrid membrane, the unique hybridization endows the ion microstructure with changes and functions, and is beneficial to reduction of methanol cross permeation and promotion of rapid proton transfer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of proton exchange membranes for fuel cells, and in particular to a proton exchange membrane and a preparation method and application thereof. Background Art

[0002] Direct methanol fuel cells (DMFCs) are ideal for portable electronic devices, vehicles, and backup power sources due to their simple operation, high energy density, and the convenience of using liquid fuel (methanol). Compared with traditional batteries and other fuel cell technologies, DMFCs not only provide clean energy but also have good environmental friendliness, so they have broad prospects in future energy applications. In direct methanol fuel cells, ion exchange membranes need to have high proton conductivity to effectively promote the conversion of electrical energy. At the same time, in order to avoid energy loss and catalyst poisoning caused by methanol cross-permeation, the membrane also needs to have low methanol permeability. In addition, good chemical and mechanical stability are key factors to ensure that the membrane maintains stable performance during long-term operation of the fuel cell. Currently, Nafion membranes are widely used in DMFCs due to their excellent proton conductivity and chemical stability. However, the methanol cross-permeation problem of Nafion membranes has not been completely solved. To this end, researchers are developing new organic-inorganic hybrid materials to reduce methanol permeation by regulating the microstructure of the materials, while improving proton conductivity and mechanical strength of the membrane. Although a variety of materials have shown certain performance advantages, how to effectively control methanol cross-permeation while improving proton conductivity in DMFC remains a key challenge. Existing membrane materials still have urgent problems to be solved in terms of durability, mechanical strength and cost-effectiveness during long-term operation (Nature 2023, 617, 299).

[0003] The Chinese patent application number CN201710102133.3 provides a sulfonated polyaryletherketonesulfone and ionic liquid composite proton exchange membrane for fuel cells and a preparation method thereof. By doping with ionic liquid, the composite membrane has higher proton conductivity and better thermal stability, and has good dimensional stability and mechanical properties. The proton conductivity of the proton exchange membrane is 0.067S / cm~0.08S / cm at 80°C, and the Young's modulus at room temperature is about 1600MPa.

[0004] The Chinese patent application number CN201010195372.6 provides a method for preparing a composite proton exchange membrane, which reduces methanol permeation and improves proton conductivity by doping polyaniline and heteropolyacid. The proton conductivity of the proton exchange membrane is (1.5~2)×10 -2 S / cm, methanol permeability (1~2.8)×10 -7 cm 2 / s.

[0005] Although the existing technology has improved in some aspects compared with Nafion membrane, it still fails to meet the long-term use requirements in terms of proton conductivity, dimensional stability, durability, mechanical strength, etc. Therefore, in order to meet the actual application needs, it is urgent to develop a better direct methanol fuel cell proton exchange membrane. Summary of the invention

[0006] In view of the existing phenomenon, the present invention provides a proton exchange membrane and a preparation method and application thereof, which at least solves one of the above technical problems.

[0007] The technical solution provided by the present application is: a proton exchange membrane, which is obtained based on sulfonated polyaryletherketonesulfone loaded hybrid filler; the hybrid filler includes polyacid and ionic liquid.

[0008] Those skilled in the art can select polyacids and ionic liquids according to their functional contributions, and the selection criteria are determined by their performance improvement for polymer membranes, such as improving proton conductivity, improving mechanical properties, or improving membrane dimensional stability.

[0009] Furthermore, the mass ratio of the sulfonated polyaryletherketonesulfone to the hybrid filler is 1:(0.01-0.5).

[0010] Furthermore, the polyacid is polyoxyvanadate.

[0011] Furthermore, the structural formula of the polyoxyvanadate is (NH 4 ) 7 [MnV 13 O 38 ].

[0012] Furthermore, the ionic liquid is 1-ethyl 3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

[0013] Furthermore, the molar ratio of the polyacid to the ionic liquid is 1:(1-5).

[0014] The second technical solution provided by the present application is: a method for preparing the above-mentioned proton exchange membrane, comprising the following steps: S1. The sulfonated polyaryletherketonesulfone and the hybrid filler are dissolved in a solvent to obtain a membrane-forming solution; S2. Drying the membrane-forming liquid to form the proton exchange membrane.

[0015] Furthermore, the preparation method of the hybrid filler is: mixing and grinding the polyacid and the ionic liquid.

[0016] Furthermore, the solvent is 1-methyl-2-pyrrolidone; step S1 specifically comprises adding the sulfonated polyaryletherketonesulfone to the solvent and stirring at room temperature for at least 12 hours, then adding a hybrid filler to obtain a mixture, and ultrasonically treating the mixture for at least 24 hours to obtain the membrane-forming solution.

[0017] The third technical solution provided by the present application is: application of the above-mentioned proton exchange membrane in a direct methanol fuel cell.

[0018] The present invention prepares a proton conductive inorganic filler based on polyacid and ionic liquid for hybridization with sulfonated poly(aryletherketonesulfone) (SPAEKS) to solve the "trade-off" problem between high proton conductivity and methanol permeability.

[0019] The present invention is a polyoxyvanadate (NH4) modified by 1-ethyl 3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM TFSI) ionic liquid. 4 ) 7 [MnV 13 O 38 ](AMV) synthesized AI (AMV-EMIM TFSI) filler is a strategy to modify soluble polyacids with water-insoluble ionic liquids to effectively reduce the solubility of polyacids. This approach does not sacrifice proton conductivity and forms a favorable chemical microenvironment for proton conduction. Due to enhanced ionic interactions, the new inorganic filler AI is uniformly dispersed and stable in the polymer matrix. This filler AI can promote a continuous hydrogen bond network within sulfonated polyaryletherketonesulfone SPAEKS, forming a favorable chemical microenvironment for proton conduction. Compared with traditional hybrid membranes, this unique hybridization imparts changes and functions in the ionic microstructure, which helps to reduce methanol cross-permeation and promote rapid proton transfer. This functionalization approach provides a versatile platform for the development of hybrid membrane materials tailored for specific applications in proton exchange membrane systems.

[0020] Compared with the prior art, the present invention has the following advantages: (1) The synthesis process is simple, and the yield of the synthesized AI filler is as high as 85%.

[0021] (2) By modifying the soluble polyacid with water-insoluble ionic liquids, its solubility is effectively reduced. This strategy has wide applicability and can be extended to reduce the solubility of other soluble polyacids.

[0022] (3) Since both AI filler and sulfonated poly(aryletherketonesulfone) are soluble in common organic solvents, physical mixing and stirring are used for doping, which is easy to operate and implement. Finally, the membrane is formed by solution casting to obtain a composite inorganic-organic proton exchange membrane material with high proton conductivity and good thermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The accompanying drawings, which are incorporated into and constitute a part of the specification, illustrate embodiments of the present invention and are used together with the description to explain the principles of the present invention. The drawings described below are some embodiments of the present invention, but not all embodiments. For those of ordinary skill in the art, other drawings can be obtained from these drawings without creative work.

[0024] Figure 1 A schematic diagram of a process flow of a proton exchange membrane embodiment; Figure 2 The conductivity of the proton exchange membrane varies with temperature; Figure 3 A graph showing the methanol permeability of a proton exchange membrane; Figure 4 This is a performance diagram of a methanol fuel cell with a proton exchange membrane; Figure 5 This is a graph of the long-term oxidation stability of the proton exchange membranes prepared in Examples 1-3 of the present invention; Figure 6 This is a diagram of the mechanical properties of the proton exchange membranes prepared in Examples 1-6 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the description of this application, unless otherwise clearly specified and limited, the terms "connected", "connected", and "fixed" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0027] In the present application, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0028] In the description of this embodiment, the terms "up", "down", "left", "right", and other orientations or positional relationships are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of description and simplification of operation, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on this application.

[0029] Embodiment 1 provides a proton exchange membrane, and its preparation method comprises the following steps: (1) Preparation of sulfonated poly(aryletherketonesulfone) (SPAEKS-15) polymer with a sulfonation degree of 15%: In a nitrogen environment, 4.5658 g of bisphenol A, 4.2549 g of 4,4'-difluorobenzophenone, 0.1518 g of 3,3'-disulfonated 4,4'-dichlorodiphenylsulfone, 5.528 g of potassium carbonate, 20 mL of toluene, and 18 mL of sulfolane were charged into a three-necked flask. The mixture was refluxed at 120 °C for 4 h and then stirred at 170 °C for another 8 h to complete polymerization. The polymer solution was poured into deionized water to obtain a white strip. Then, the strip was cut and washed three times in boiling water for purification. Finally, SPAEKS-15 was dried in an oven at 60 °C for 24 h.

[0030] (2) Synthesis of polyacid AMV: 6.083 g of ammonium metavanadate was dissolved in 180 mL of deionized water at 85 °C, and then 4 mL of 1 mol L-1 nitric acid, 4 mL of 1 mmol L-1 manganese sulfate, and 1.826 g of ammonium persulfate were added. After magnetic stirring at 80 °C for 5 h, the mixed solution was evaporated to about 40 mL and then treated with 0.6 g of ammonium acetate. After filtering out solid impurities, the filtrate was continuously stirred and precipitated at 0 °C to obtain orange crystals. The product was washed with ethanol / water (1:1 v / v) solution and the orange crystalline material was collected. To prepare AMV nanoparticles, 0.2 g of the prepared AMV powder was first dissolved in 10 mL of distilled water. Then, 50 mL of ethanol was added dropwise to the solution, and nanoparticles appeared. Then, the product was obtained by centrifugation and washed with ethanol. To remove moisture from the powder, the prepared and recrystallized product was dried at 120 °C for 1 h.

[0031] (3) Synthesis of filler AI: 0.145 g AMV and 0.275 g 1-ethyl-3-methylimidazolium bis(trifluoromethyl) yellow imide ionic liquid were ground in an agate mortar for 4 h to synthesize a yellow viscous 1-ethyl-3-methylimidazolium polyoxyvanadate composite material (abbreviated as AI).

[0032] (4) Preparation of organic-inorganic hybrid proton exchange membrane: SPAEKS-15 (0.5 g) was dissolved in NMP (10 mL) and stirred at room temperature for 24 h. Then 0.025 g of AI was added and the mixture was sonicated for 48 h to obtain a homogeneous solution. The membrane was prepared by solution casting on a glass plate (8 × 8 cm 2 ). The mixed film was placed in a vacuum oven at 60 °C for 24 hours to remove the solvent. The thickness of the film ranged from 35 μm and the film was named SPAEKS-15 / AI-5.

[0033] Embodiment 2 provides a proton exchange membrane, and its preparation method comprises the following steps: (1) Preparation of sulfonated poly(aryletherketonesulfone) (SPAEKS-30) polymer with a sulfonation degree of 30%: In a nitrogen environment, 4.5658 g of bisphenol A, 3.7094 g of 4,4'-difluorobenzophenone, 1.5188 g of 3,3'-disulfonated 4,4'-dichlorodiphenyl sulfone, 5.528 g of potassium carbonate, 20 mL of toluene and 18 mL of cyclopentane were charged into a three-necked flask. The mixture was refluxed at 120 °C for 4 h and then stirred at 170 °C for another 8 h to complete polymerization. The polymer solution was poured into deionized water to obtain a white strip. Then, the strip was cut and washed three times in boiling water for purification. Finally, SPAEKS-30 was dried in an oven at 60 °C for 24 h. (2) Polyacid AMV synthesis: The same method as the AMV synthesis method in Example 1 (3) Filler AI synthesis: the same as the AI ​​synthesis method in Example 1 (4) Preparation of organic-inorganic hybrid proton exchange membrane: SPAEKS-30 (0.5 g) was dissolved in NMP (10 mL) and stirred at room temperature for 24 h. Then 0.025 g of AI was added and the mixture was sonicated for 48 h to obtain a homogeneous solution. The membrane was prepared by solution casting on a glass plate (8 × 8 cm 2 ). The mixed film was placed in a vacuum oven at 60 °C for 24 hours to remove the solvent. The thickness of the film ranged from 33 μm and the film was named SPAEKS-30 / AI-5.

[0034] Embodiment 3 provides a proton exchange membrane, and its preparation method comprises the following steps: (1) Preparation of sulfonated poly(aryletherketonesulfone) (SPAEKS-50) polymer with a sulfonation degree of 50%: In a nitrogen environment, 4.5658 g of bisphenol A, 3.2730 g of 4,4'-difluorobenzophenone, 2.5313 g of 3,3'-disulfonated 4,4'-dichlorodiphenylsulfone, 5.528 g of potassium carbonate, 20 mL of toluene and 18 mL of sulfolane were charged into a three-necked flask. The mixture was refluxed at 120 °C for 4 h and then stirred at 170 °C for another 8 h to complete polymerization. The polymer solution was poured into deionized water to obtain a white strip. Then, the strip was cut and washed three times in boiling water for purification. Finally, SPAEKS-50 was dried in an oven at 60 °C for 24 h.

[0035] (2) Synthesis of polyacid AMV: The method of synthesizing AMV is the same as that in Example 1.

[0036] (3) Filler AI synthesis: The AI ​​synthesis method is the same as that in Example 1.

[0037] (4) Preparation of organic-inorganic hybrid proton exchange membrane: SPAEKS-50 (0.5 g) was dissolved in NMP (10 mL) and stirred at room temperature for 24 h. Then 0.025 g of AI was added and the mixture was sonicated for 48 h to obtain a homogeneous solution. The membrane was prepared by solution casting on a glass plate (8 × 8 cm 2 ). The mixed film was placed in a vacuum oven at 60 °C for 24 hours to remove the solvent. The thickness of the film ranged from 28 μm and the film was named SPAEKS-50 / AI-5.

[0038] Comparative Example 1 provides a proton exchange membrane, and its preparation method comprises the following steps: (1) Preparation of sulfonated poly(aryletherketonesulfone) (SPAEKS-15) polymer with a sulfonation degree of 15%: In a nitrogen environment, 4.5658 g of bisphenol A, 4.2549 g of 4,4'-difluorobenzophenone, 0.1518 g of 3,3'-disulfonated 4,4'-dichlorodiphenylsulfone, 5.528 g of potassium carbonate, 20 mL of toluene, and 18 mL of sulfolane were charged into a three-necked flask. The mixture was refluxed at 120 °C for 4 h and then stirred at 170 °C for another 8 h to complete polymerization. The polymer solution was poured into deionized water to obtain a white strip. Then, the strip was cut and washed three times in boiling water for purification. Finally, SPAEKS-15 was dried in an oven at 60 °C for 24 h.

[0039] (2) Preparation of proton exchange membrane: SPAEKS-15 (0.5 g) was dissolved in NMP (10 mL) and stirred at room temperature for 24 h. The mixture was sonicated for 48 h to obtain a homogeneous solution. The membrane was prepared by solution casting on a glass plate (8 × 8 cm 2 ). The mixed film was placed in a vacuum oven at 60 °C for 24 h to remove the solvent. The thickness of the film ranged from 33 μm and the film was named SPAEKS-15.

[0040] Comparative Example 2 provides a proton exchange membrane, and its preparation method comprises the following steps: (1) Preparation of sulfonated poly(aryletherketonesulfone) (SPAEKS-30) polymer with a sulfonation degree of 30%: In a nitrogen environment, 4.5658 g of bisphenol A, 3.7094 g of 4,4'-difluorobenzophenone, 1.5188 g of 3,3'-disulfonated 4,4'-dichlorodiphenylsulfone, 5.528 g of potassium carbonate, 20 mL of toluene, and 18 mL of sulfolane were charged into a three-necked flask. The mixture was refluxed at 120 °C for 4 h and then stirred at 170 °C for another 8 h to complete polymerization. The polymer solution was poured into deionized water to obtain a white strip. Then, the strip was cut and washed three times in boiling water for purification. Finally, SPAEKS-30 was dried in an oven at 60 °C for 24 h.

[0041] (2) Proton exchange membrane preparation: SPAEKS-30 (0.5 g) was dissolved in NMP (10 mL) and stirred at room temperature for 24 h. The mixture was sonicated for 48 h to obtain a homogeneous solution. The membrane was prepared by solution casting on a glass plate (8 × 8 cm 2 ). The mixed film was placed in a vacuum oven at 70 °C for 24 h to remove the solvent. The thickness of the film ranged from 30 μm and the film was named SPAEKS-30.

[0042] Comparative Example 3 provides a proton exchange membrane, and its preparation method comprises the following steps: (1) Preparation of sulfonated poly(aryletherketonesulfone) (SPAEKS-50) polymer with a sulfonation degree of 50%: In a nitrogen environment, 4.5658 g of bisphenol A, 3.2730 g of 4,4'-difluorobenzophenone, 2.5313 g of 3,3'-disulfonated 4,4'-dichlorodiphenylsulfone, 5.528 g of potassium carbonate, 20 mL of toluene and 18 mL of sulfolane were charged into a three-necked flask. The mixture was refluxed at 120 °C for 4 h and then stirred at 170 °C for another 8 h to complete polymerization. The polymer solution was poured into deionized water to obtain a white strip. Then, the strip was cut and washed three times in boiling water for purification. Finally, SPAEKS-50 was dried in an oven at 60 °C for 24 h.

[0043] (2) Proton exchange membrane preparation: SPAEKS-50 (0.5 g) was dissolved in NMP (10 mL) and stirred at room temperature for 24 h. The mixture was sonicated for 48 h to obtain a homogeneous solution. The membrane was prepared by solution casting on a glass plate (8 × 8 cm 2 ). The mixed film was placed in a vacuum oven at 70 °C for 24 h to remove the solvent. The thickness of the film ranged from 27 μm and the film was named SPAEKS-50.

[0044] The conductivity curves of Examples 1-3 and Comparative Examples 1-3 as a function of temperature are shown in the attached figure. Figure 2 The conductivity, i.e., the in-plane proton conductivity, was measured by electrochemical impedance spectroscopy in the frequency range of 0.1 Hz to 1 MHz using a quadrupole probe method using an Autolab (AUT86925) electrochemical workstation. The membrane was cut into rectangular pieces (40 × 10 mm 2 ), the tests were conducted at different temperatures, the experiments were tested in water and exposed to air. The conductivity (σ) is calculated as follows: σ = L / RS, where L is the distance between the two electrodes, R is the resistance of the membrane, and S is the cross-sectional area of ​​the membrane.

[0045] By the attached Figure 2 It can be seen that the hybrid filler AI significantly improves the conductivity of SPAEKS. The proton exchange membrane provided in the present application has a relatively high conductivity. It can also be seen that SPAEKS-50 / AI-5 obtained in Example 3 is the embodiment with the highest conductivity.

[0046] The methanol permeability images of the proton exchange membranes obtained in Example 3 and Comparative Example 3 are shown in the attached figure. Figure 3 The methanol permeability test method is as follows: the two chambers separated by the membrane are filled with equal amounts of deionized water and 10M methanol solution respectively. Methanol is permeated for 2 hours under magnetic stirring. The methanol concentration in the water chamber is tested using a gas chromatograph (Agilent 6890N), and the methanol permeation rate of the membrane is calculated as follows: C B =APCA T / V B L, where A (cm 2 ) is the effective area of ​​the membrane involved in methanol permeation, P (cm 2 / s) is the methanol permeation rate, C B (mol / L) and C A (mol / L) are the concentrations of methanol in the water chamber and the methanol chamber, respectively, V B (mL) is the volume of the single chamber, L (cm) is the thickness of the membrane, and T (s) is the methanol permeation time.

[0047] By the attached Figure 3 It can be seen that the AI ​​hybrid filler of the present application significantly reduces the methanol permeability of SPAEKS-50 and improves the selectivity.

[0048] The performance diagram of the methanol fuel cell of SPAEKS-50 / AI-5 proton exchange membrane of Example 3 is shown in the attached figure. Figure 4 , it can be seen that the present application can be well applied to methanol fuel cells. Methanol fuel cell performance experimental method: For membrane electrode assembly, Pt-Ru / C and Pt / C were used as anode and cathode, respectively. The catalyst ink was prepared by mixing the catalyst and 10% relative weight of Nafion binder in isopropanol / deionized water (1:1). The catalyst was sprayed on both sides of the membrane sample using an ultrasonic atomizing sprayer (SP202). The Pt-Ru / C loading was 4 mg / cm 2 , Pt / C loading is 2 mg / cm 2 After drying, a catalyst coated membrane (CCM) was obtained. Then the gas diffusion layer (GDL) was pressed on both sides of the CCM. The active area of ​​the membrane electrode was 4 cm 2 The cathode side was fed with humidified oxygen at a flow rate of 300 sccm, and the anode side was fed with methanol solution (2 mol / L) at a flow rate of 33.33 mL / min.

[0049] The long-term oxidation stability diagram of the proton exchange membrane prepared in Examples 1-3 is summarized as follows Figure 5 The long-term oxidation stability of the proton exchange membrane was tested by immersing the dried membrane in Fenton's reagent (3% H 2 O 2 and 2ppm ferrous sulfate). The weight before and after the oxidation test was recorded to determine the oxidation resistance. The oxidation stability was calculated as follows: Wos = Wr / Wo × 100%, where Wo is the initial dry film weight (g) and Wr is the remaining weight of the film after oxidation (g).

[0050] It can be seen that the proton exchange membrane prepared in the present application has good long-term oxidation stability and can maintain its performance during long-term operation.

[0051] The mechanical properties of the proton exchange membranes prepared in Examples 1-3 and Comparative Examples 1-3 are summarized as follows: Figure 6 . Test method for mechanical properties of proton exchange membrane: The tensile modulus of the sample was evaluated using a tensile tester (Instron 5965) at a tensile rate of 1 mm / min at room temperature. Before testing, the sample was cut into 5 mm × 5 cm strips, and the sample was immersed in deionized water for storage. Before the test, the moisture on the surface of the membrane was wiped off. Each sample was tested 5 times under the same test conditions for analysis. It can be seen that the proton exchange membrane prepared in this application has a good elongation at break performance, and the mechanical properties of the proton exchange membrane are significantly improved after doping with AI filler.

[0052] In summary, the present invention prepares a proton exchange membrane based on sulfonated polyaryletherketonesulfone loaded with polyacid-ionic liquid hybrid filler. By selecting water-insoluble ionic liquid to modify soluble POM, the solubility of POM is effectively reduced. This method does not sacrifice proton conductivity, forms a favorable chemical microenvironment for proton conduction, and is a functional filler implementation method with strong predictability.

[0053] For example, polyoxyvanadate (NH 4 ) 7 [MnV 13 O 38 The invention relates to a proton exchange membrane with a proton conductive inorganic filler composed of a polyacid of Mg(III) (AMV) and an ionic liquid such as 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM TFSI) to solve the "trade-off" problem between high proton conductivity and methanol permeability, and to improve durability and mechanical strength during long-term operation.

[0054] The contents described above may be implemented individually or in combination in various ways, and these variations are all within the protection scope of the present invention.

[0055] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or device comprising the elements.

[0056] The above contents are further detailed descriptions of the present invention in combination with specific preferred implementation modes, and it cannot be determined that the specific embodiments of the present invention are limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.

Claims

1. A proton exchange membrane, characterized in that: The invention is obtained based on sulfonated polyaryletherketonesulfone loaded hybrid filler; the hybrid filler comprises polyacid and ionic liquid.

2. The proton exchange membrane according to claim 1, characterized in that The mass ratio of the sulfonated polyaryletherketonesulfone to the hybrid filler is 1:(0.01-0.5).

3. The proton exchange membrane according to claim 1, characterized in that The polyacid is polyoxyvanadate.

4. The proton exchange membrane according to claim 3, characterized in that The structural formula of the polyoxyvanadate is (NH4)7[MnV 13 O 38 ].

5. The proton exchange membrane according to claim 1, characterized in that: The ionic liquid is 1-ethyl 3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

6. The proton exchange membrane according to claim 1, characterized in that: The molar ratio of the polyacid to the ionic liquid is 1:(1-5).

7. A method for preparing a proton exchange membrane according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1. The sulfonated polyaryletherketonesulfone and the hybrid filler are dissolved in a solvent to obtain a membrane-forming solution; S2. Drying the membrane-forming liquid to form the proton exchange membrane.

8. The preparation method according to claim 7, characterized in that: The preparation method of the hybrid filler is: mixing and grinding the polyacid and the ionic liquid.

9. The preparation method according to claim 7, characterized in that: The solvent is 1-methyl-2-pyrrolidone; step S1 specifically comprises adding the sulfonated polyaryletherketonesulfone to the solvent and stirring at room temperature for at least 12 hours, then adding a hybrid filler to obtain a mixture, and ultrasonically treating the mixture for at least 24 hours to obtain the membrane-forming solution.

10. Use of the proton exchange membrane according to any one of claims 1 to 6 in a direct methanol fuel cell.

Citation Information

Patent Citations

  • Preparation method of composite proton exchange membrane

    CN101864163A

  • Sulfonated poly(aryl ether ketone sulfone) and ionic liquid composite type PEM (proton exchange membrane) for FCs (fuel cell) and preparation method of PEM

    CN106832369A